EFFECTIVE LEADERSHIP: Building a Positive Academic Culture - Wahyudi, Wahyudi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
In the organizational context, leadership assumes a pivotal role as a foundational element in executing functions and wielding authority. Occupying positions of prominence and wielding significant authority, leaders possess the capacity to effectively oversee and guide the organization. The leader's strategic positioning is indispensable, rendering them a key ally in advancing the collective interests of the organization's various echelons, ranging from the grassroots to the uppermost tiers, with a steadfast commitment to objective-oriented pursuits. This research endeavors to scrutinize the responses, perceptions, and evaluations of lecturers regarding the leadership exhibited by heads of study programs, thereby furnishing a comprehensive and contextual comprehension of the intricacies of leadership dynamics. The study was conducted at Pamulang University, focusing on the Undergraduate Management study program within the Faculty of Economics and Business. Primary respondents comprised level one lecturers who concurrently served as developers of the study program. Employing a simple random sampling technique facilitated by the distribution of direct questionnaires, the research data underwent analysis through qualitative descriptive methods. Findings from the research reveal that the leadership style demonstrated by the head of the Undergraduate Management study program at the Faculty of Economics and Business embodies democratic characteristics. This is evidenced by the active involvement of developer lecturers in all facets of the tri dharma activities and the decision-making processes inherent to the study program.